Case reportJuvenile xanthogranuloma: a rare benign histiocytic disorder - Szczerkowska-Dobosz, Aneta; Kozicka, Dorota; Purzycka-Bogdan, Dorota; Biernat, Wojciech; Stawczyk, Marta; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Juvenile xanthogranuloma (JXG) is a rare histiocytic disorder that typically affects children. The clinical presentation of this disease is characterized by single or, rarely, multiple yellow and brown skin nodules, most often found on the face and neck. Internal organ involvement has been sporadically observed in JXG and is associated with an increased risk of serious complications. We report two cases with a small and large nodular form of JXG.